Expert systems the fifth generation - more than a genealogical pursuit - Muller, Marius (Acta Structilia, 1995)
This article describes the nature of Expert Systems and outlines their possible use in the field of building economics. Their usefulness in terms of quantification of uncertainty is also examined. It was found that the benefits of developing Expert Systems are tremendous, but that the success of Expert Systems would be determined by their acceptance by the general public.